Perceptions of mothers about food allergy - A preliminary report - Endy P. Prawirohartono (Indonesian Pediatric Society, 2001)
The impact of food allergy on child growth and development should be properly evaluated, although the prevalence of food allergy is low. Most mothers in Indonesia still Â practice food elimination if their children are suspected to suffer from food allergy. Types of food that are usually avoided are high-class protein sources such as egg, milk, beef and fish. These types of foods are important for maintaining growth and development during childhood. The aim of this study is to know the perceptions of mothers about food allergy, including its pathophysiology, clinical symptoms and signs, management, and types of foods as allergens. Among mostly 114 of medium to highly educated mothers, there were still wrong perceptions about food allergy. From 114 mothers, 48.2% of them believed that food allergy can not be inherited, egg causes furuncle (54.3%), breast milk causes atopic eczema (46.5%), and food allergy does not relate to respiratory symptoms. There was a relationship between these perceptions and mothersâ€™ educational level. Skin manifestations were most popular among mothers, whereas only 37.7% of mothers believed that food allergy can causes respiratory symptoms. Egg, shrimp, fish, and shellfish were types of animal foods which were popular, whereas peanut, soy, banana, rice and vegetables were recognized as the major causes of food allergy among non animal products.